2018
DOI: 10.1111/hepr.13253
|View full text |Cite
|
Sign up to set email alerts
|

Dysbalanced sex hormone status is an independent predictor of decompensation and mortality in patients with liver cirrhosis

Abstract: Aims: Endocrinological abnormalities, including low testosterone levels, are prevalent in cirrhosis. We assessed sexual hormone status in regard to hemodynamic abnormalities and its impact on hepatic decompensation and survival.Methods: Males with cirrhosis were prospectively included in this study since 2010. Sexual hormones including bioavailable testosterone, total testosterone, luteinizing hormone, folliclestimulating hormone, prolactin, and sex hormone-binding globulin as well as Child-Pugh score, Model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Although sex did not appear to modify the effect of HSD17B13 genotype on liver‐related events, we investigated serum testosterone levels in cohort B. Interestingly, we observed numerically lower serum levels of testosterone (Figure S4) in male patients harbouring the loss‐of‐function TA allele. As low testosterone levels have repeatedly been linked to liver‐related events by our group and others, a potential detrimental impact of the HSD17B13 TA allele in patients with ACLD via decreased testosterone biosynthesis warrants further study in a larger series of patients.…”
Section: Discussionmentioning
confidence: 85%
“…Although sex did not appear to modify the effect of HSD17B13 genotype on liver‐related events, we investigated serum testosterone levels in cohort B. Interestingly, we observed numerically lower serum levels of testosterone (Figure S4) in male patients harbouring the loss‐of‐function TA allele. As low testosterone levels have repeatedly been linked to liver‐related events by our group and others, a potential detrimental impact of the HSD17B13 TA allele in patients with ACLD via decreased testosterone biosynthesis warrants further study in a larger series of patients.…”
Section: Discussionmentioning
confidence: 85%
“…Giving the detrimental effects of sarcopenia on liver‐related outcomes and mortality in patients with ACLD, reversing muscle‐loss represents a management priority in these patients . Sarcopenia in ACLD is multifactorial and the pathophysiology include protein‐malnutrition, increased proteolysis from skeletal muscles, accelerated starvation response, physical inactivity or humoral factors such as upregulation of myostatin as a result of hyperammonaemia or hypotestosteronism . Nutritional supplementation with branched chain amino acids (BCAAs) has been shown to improve liver‐related outcomes and muscle mass .…”
Section: Discussionmentioning
confidence: 99%
“…Women with sarcopenia may be at a more advanced stage of malnutrition because they have reached the point of requiring their muscle mass as an energy store. Also, the androgens deficiencies with hyperestrogenism in male patient with liver cirrhosis play a role in muscle status deterioration 23 . Also, we found that there was significant difference as regard BMI estimated by dry weight between sarcopenic and non sarcopenic patients (p<0.001) as all patients (100%) with low body weight (BMI<18.5) were sarcopenic.…”
Section: Discussionmentioning
confidence: 99%